Copolymers of 7-Methoxy-2-Acetyl Benzofuryl Methylmethacrylate With Styrene: Synthesis, Characterization, Reactivity Ratios and Determination of Kinetic Parameters With Thermogravimetric Analysis - Ilter, Zulfiye; Soykan, Cengiz; Solmaz, Adnan (Taylor & Francis Inc, 2015)
The 7-methoxy-2-acetyl benzofuryl methylmethacrylate (MABMM) monomer was synthesized by reacting 7-methoxy-2-bromo acetyl benzofurane with sodium methacrylate in acetonitrile solvent at 70 degrees C in the presence of triethylbenzylammoniumchloride (TEBAC). The monomer was characterized by FTIR, H-1-and C-13-NMR spectral studies. Reactivity ratios for the copolymers 7-methoxy-2-acetyl benzofuryl methylmethacrylate (MABMM)-co- styrene (ST) are reported. Copolymers were prepared by free radical polymerization using 2,2 '-azobisisobutyronitrile (AIBN) as an initiator at 70 degrees C in 1,4-dioxane solution. FTIR, H-1-and C-13-NMR spectral studies and gel permeation chromatography (GPC) were used the copolymer characterization. The monomer compositions in the copolymer were determined by elementel analyses and the reactivity ratios (ri) were calculated applying diverse linear methods, namely Finemann-Ross (FR) and Kelen-Tudos (KT) and the nonlinear error invariable model method of a computer program RREVM. By using the latter pr degrees Cedure, the values of the reactivity ratios were estimated as 2.74 and 0.69 for the system MABMM (1) and ST (2), respectively. These values suggest the formation of nearly-alternating copolymers in the systems. Molecular weights were determined by gel permeation chromatography (GPC). The polydispersity indices of the polymers determined using suggest a strong tendency for chain termination by disproportionation. The glass transition temperature of the polymers were investigated by Shimadzu DSC-60 and the apparent thermal decomposition activation energies (E-d) were calculated by the Ozawa method using the Perkin-Elmer TGA thermobalance, respectively. Tg increases when the concentration of polar monomer (MABMM) in the copolymer increases. It was observed that thermal stabilities of copolymers increased with increasing of MABMM content in copolymers.
Keywords: thermogravimetric analysis; monomer reactivity ratios; 7-Methoxy-2-acetyl benzofuryl methylmethacrylate (MABMM)